Vitamin D improves hepatic alterations in ACE1 and ACE2 expression in experimentally induced metabolic syndrome - Sara Mohater; Samar Qahtan; Zienab Alrefaie; Ahlam Alahmadi (Saudi Pharmaceutical Journal, 2023)
Metabolic Syndrome (MetS) is a term used to describe a cluster of pathophysiological, biochemical, and metabolic criteria; including high Blood Pressure (BP), high cholesterol, dyslipidaemia, central obesity and Insulin Resistance (IR). The Renin Angiotensin System (RAS) has a regulatory function in BP, hydroelectrolyte balance, and cardiovascular function. RAS is composed of angiotensinogen (AGT), (Ang I), (Ang II), (ACE1), (ACE2), (AT1R), (AT2R), and (Ang 1–7). Vitamin D had been proved to act as a protective factor against MetS. Therefore, the study is pursued to explore vitamin D supplementation roles on hepatic RAS in MetS experimental model. At first, 36 males Albino rats were separated into 4 groups and induced to MetS under controlled circumstances for 3 months. Then, data were collected from blood samples, whereas RNA extracted from liver were analyzed using biochemical and statistical analysis tests. As a result, the major finding was proving that vitamin D can balance the expression of ACE1 and ACE2. Also, confirming that it can improve MetS components by elevating HDL and insulin levels while reducing the levels of BP, cholesterol, LDL, TG, GLU, ALT, AST, and IR. These outcomes may give a new insight into the RAS pathways associated with MetS.